Comparative Effectiveness of Tamarind (Tamarindus indica) and Starfruit (Averrhoa bilimbi) Solutions in Reducing Lead (Pb) Levels in Shellfish (Polymesoda erosa) - A Mirnayanti; Mary Grace B Maribao; San Techly (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the effectiveness of soaking duration in tamarind (Tamarindus indica) and starfruit (Averrhoa bilimbi) solutions in reducing the concentration of heavy metal lead (Pb) in shellfish (Polymesoda erosa) before and after treatment. Methodology: This study employed a descriptive method using Atomic Absorption Spectrophotometry (AAS) to measure Pb levels in Polymesoda erosa clams. Samples from Paotere Market, Makassar, were soaked in tamarind or starfruit solutions for 30, 60, and 90 minutes, then analyzed using AAS at a wavelength of 217.0 nm. Main Findings: Soaking Polymesoda erosa in tamarind solution for 30, 60, and 90 minutes reduced Pb levels by 30.69%, 40.92%, and 50%, respectively. Soaking in starfruit solution for the same durations reduced Pb levels by 19.32%, 65.91%, and 93.18%, respectively. Starfruit solution soaking for 90 minutes achieved Pb levels below the permissible consumption limit. Novelty/Originality of this study: This study introduces the comparative use of tamarind (Tamarindus indica) and starfruit (Averrhoa bilimbi) solutions to reduce Pb levels in Polymesoda erosa. It reveals starfruit’s superior effectiveness due to higher citric acid content, offering a simple, natural, and low-cost method for heavy metal reduction in seafood, potentially improving food safety in coastal communities.